1961
DOI: 10.1128/aem.9.2.108-110.1961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tylosin and Nisin on Canned Food Spoilage Bacteria

Abstract: Many antibiotics have been screened for inhibition of sporeforming bacteria during the last 10 years in this laboratory. The effect of some of these antibiotics on canned food spoilage bacteria has previously been described (Denny and Bohrer, 1959). Recently, two antibiotics which eventually may be of use in food processing have been through a preliminary screening in this laboratory. These antibiotics are nisin and tylosin. Nisin has been recommended for approval for use in certain foods in Great Britain (Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…of nisin/ml. Denny et al (1961) showed that 4,000 I.U. of nisin/ml were required to eliminate outgrowth of strains 62A and 213B when 20,000 spores/ml were inoculated into a tryptone beef extract medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of nisin/ml. Denny et al (1961) showed that 4,000 I.U. of nisin/ml were required to eliminate outgrowth of strains 62A and 213B when 20,000 spores/ml were inoculated into a tryptone beef extract medium.…”
Section: Discussionmentioning
confidence: 99%
“…While Jarvis (1967) reports that B. stearothermophilus spores are inhibited by less than 2 I.U. of nisin/ml, Denny et al (1961) reported that 1,000 I.U. of nisin/ml was required to inhibit spore outgrowth by a particular strain of B. stearothermophilus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The destruction of spore-forming bacteria by Tylosin has been reported by Denny et al (1961) and by Greenberg and Silliker (1961).…”
mentioning
confidence: 57%
“…Tylosin is a new antimicrobial agent that has been described previously (Hamill et al, 1961;McGuire et al, 1961). An earlier observation by Malin (1958) of the destruction of sporeforming bacteria by tylosin has been confirmed by Denny et al (1961b) and by Greenberg and Silliker (1962). There is disagreement on the mode of action of tylosin.…”
Section: Introductionmentioning
confidence: 71%